Reconstruction of Prevention and Handling of Stunting Policy in Public Health Center - Retno Widhiastuti; Mahmutarom HR; Setyo Trisnadi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Indonesia has severe nutritional problems, one of which is stunting. Stunting is a chronicmalnutrition condition caused by many multi-dimensional. According to the Minister of Health Republicof Indonesia No. 43 of 2019 about Public Health Center, Public Health Center Services are part of publicservices and are basic routine health services consisting of Public Health Efforts (UKM) and IndividualHealth Efforts (UKP), one of which is the prevention and handling of stunting in Public Health Center.Demak III Public Health Center is a health center in the city that has an area of 18.78 km with a populationof 38,218 people precisely on the road Cempaka Raya No. 5 Katonsari, Demak consists of 5 villages and1 village namely Kalikondang village, Katonsari, Donorojo, Mangunjiwan, Cabean, and Tempuran. Of thesix villages, Donorejo village is the village that has the highest number of stunting cases compared to othervillages.Research Objectives: The purpose of this study is to find out and analyze the reconstruction of preventionand handling of stunting policy in Public Health Center.Research Methods: This research uses the paradigm of constructivism, which is the policies that exist ingovernment agencies can be examined objectively related to accurate data, then constructed through theconcept of law that is only tested again its strength. Methods used with Critical thinking. Critical thinkingis the ability to think clearly and rationally, understand the logical relationship between ideas. The samplingmethod is a non-random sampling technique that is purposive sampling is a way of taking subjects based ona specific goal.Results and Discussion: The description of the reconstruction of prevention and handling of stunting policyin Public Health Center through integration actions with stakeholders of government agencies in the DemakRegency area is still partial. With the policy that is still partial, in the prevention and handling of stunting bycriticizing (critical thinking) existing policies. Prevention and reduction of stunting is carried out by healthworkers through programs with cross-sectors and networks already running.